The transmembrane region of CLIC1 is helical in membrane-mimetic solvents - Ngubane, Nomxolisi Chloe Mina-Liz (My University, 2012)
CLIC1 is a member of the chloride intracellular channel proteins (CLICs), a group of amphitropic chloride channels. CLICs are able to transform from a cytoplasmic form to a membrane-bound form by a mechanism thought to involve a structural rearrangement, facilitated by movement to a low pH environment, that reveals the hydrophobic transmembrane region (TMR) in the N-domain. The TMR forms an alpha-helix-beta-strand structure in the soluble CLIC1 which is then thought to form the transmembrane helix in the membrane. The aim was to characterise the structure and stability of two peptides containing the TMR in membrane-mimetic solvents using far-UV circular dichroism and fluorescence. The first peptide, β1-TMR, corresponding to the first 52 amino acids of CLIC1 was to be purified from a fusion protein with GST, obtained from overexpression in bacterial culture. The second peptide, a synthetic 30 residue peptide corresponding to the sequence range Cys24-Val46 and referred to as the TMR peptide was commercially obtained. Overexpression and purification of the GST fusion protein as well as liberation of the β1- TMR from the fusion partner using thrombin was achieved but isolation of the β1-TMR peptide from GST proved unsuccessful. Sodium dodecyl sulphate (SDS) and 2,2,2- trifluoroethanol (TFE) were used as membrane mimetics to observe the structure of the TMR peptide. The secondary structure of the peptide increased with increasing TFE and SDS concentrations until 40% TFE where it was ~52% helical and 16 mM SDS where it was ~22% helical. pH had no effect on the secondary or tertiary structure of the peptide. Chemical and thermal denaturation of the TMR revealed that the helix formed in the membrane environment followed a non-cooperative unfolding pathway over a large temperature and denaturant range, indicating a very stable structure as would be required for a transmembrane helix. These results suggest that the TMR would form a stable transmembrane helix of CLIC1 in the hydrophobic environment of the membrane as a result structural elsewhere in the mature protein facilitate by a change in pH.